Strategic Dimensions of Shatt al-Arab Coastal Road (A Study in Transport Geography) - Assist. Lect . Dr. Abdulwadood Abdulredha Abid , Assist. Lect . Dr. Abdulwadood (Basra studies journal, 2025)
The coastal road of Shatt al-Arab is one of the strategic projects that will enhance the local and regional status of Shatt al-Arab, as it contains political importance, as it forms a border strip between the two republics (i. e. Iraq and Iran) with a distance of approximately (91) km. It also has great economic importance in attracting many basic activities that are practiced by the residents of the villages adjacent to it. Its extension for a distance of (96) kilometers starting from the location of station (0,0) in the village of Abu Flus to station (96) in Ras Al-Bisha, which is the farthest point on the southern borders of Iraq in the district of Al-Faw. The possibility of extending it to the location of the presidential palaces of the former regime in Al-Barad’iya will have a positive dimension represented by it being a second bridge linking the south of Basra Governorate and its center. This will reduce traffic congestion on the parallel road, and will also contribute to the ease of access between these two points, as it is a shortcut between them, not to mention its touristic importance, which could attract tourists from inside and outside Iraq if the river transport project is rehabilitated.